2021
DOI: 10.1037/pap0000332
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic effects beyond diagnosis: The impact of dissociation on the mind–body–brain system.

Abstract: Trauma-related disorders and their related phenomena remain a fundamental quibble in the psychopathological diagnosis. Only the Psychodynamic Diagnostic Manual-2 recognizes the long time enduring effects of trauma of human hand as distinct from accidents or natural catastrophes, while the Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) does not. A response to trauma of human hand with effects on the mind-body-brain system is dissociation, a psychic mechanism denied for many years from Freud but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…This process calls into account the role of the therapist that here works at the edges of different affectives and self-states characterized by their respective time-scale and space-scale. The primary purpose of the therapist is to reach and integrate their clients’ dissociated spatiotemporal layers of self with their respective affects and thoughts (this is consistent with the work on different traumatic levels that has been clinically described by Mucci, 2013 , 2018 ; Mucci and Scalabrini, 2021 ).…”
Section: Part Iv: “Project For a Spatiotemporal Neuroscience” – Extending Freud And Solmssupporting
confidence: 56%
“…This process calls into account the role of the therapist that here works at the edges of different affectives and self-states characterized by their respective time-scale and space-scale. The primary purpose of the therapist is to reach and integrate their clients’ dissociated spatiotemporal layers of self with their respective affects and thoughts (this is consistent with the work on different traumatic levels that has been clinically described by Mucci, 2013 , 2018 ; Mucci and Scalabrini, 2021 ).…”
Section: Part Iv: “Project For a Spatiotemporal Neuroscience” – Extending Freud And Solmssupporting
confidence: 56%
“…Child abuse, especially CSA, played a key role in the manifestation of dissociation [ 76 ]. Dissociation is a mental process where there is a disconnection or a separation from thoughts, feelings, memories, and surroundings that affect an individual’s sense of identity and perception of time [ 77 ]. The current study found a negative correlation between dissociation and the nose indicator (indicating feelings of insecurity, inadequacy, and inferiority).…”
Section: Discussionmentioning
confidence: 99%
“…Mucci’s model of interpersonal trauma ( Mucci, 2018 ; Mucci and Scalabrini, 2021 ) suggests that early relational trauma (ERT) that occurs as a consequence of poor attunement between the mother and child can lead to psychopathology that renders the mother unable to provide the care required for the child’s optimal development. Lack of attunement may lead to affect dysregulation which can leave the child vulnerable to drug and alcohol abuse, eating disorders, interpersonal difficulties, and impulsivity.…”
Section: Temporospatial Dynamics In Neurosciencementioning
confidence: 99%